2018
DOI: 10.1158/0008-5472.can-17-3046
|View full text |Cite
|
Sign up to set email alerts
|

Plk1-Mediated Phosphorylation of TSC1 Enhances the Efficacy of Rapamycin

Abstract: The AKT/TSC/mTOR axis is an important pathway controlling cell growth, survival, and proliferation in response to extracellular cues. Recently, it was reported that AKT activity fluctuates across the cell cycle. However, it remains unclear whether downstream targets of AKT are also regulated by the cell cycle. Here, we report that mTORC1 activity inversely correlates with AKT activity during the cell cycle. Mechanistically, Plk1 phosphorylation of TSC1 at S467 and S578 interfered with TSC1/TSC2 binding, destab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Hypoxia-induced autophagy has been demonstrated to be crucial for survival of liver CD133+ CSCs; more interestingly, in pancreatic CSCs, HIF-1 α -dependent autophagy is critical for the equilibrium between non-stem pancreatic cancer cells and pancreatic CSCs [59]. Indeed, autophagy was found to be upregulated in multiple human AML cell lines and primary blasts after prolonged exposure to hypoxia; also, inhibition of the late-stage of autophagy overcomes Leukemia Stem Cells (LSCs) survival and chemoresistance [60, 61]. This highlights the controversial role of autophagy in the death/survival of leukemic cells, in which reduced autophagy appears to be an adaptive mechanism that accelerates AML development [62].…”
Section: Autophagy and Cancer Stem Cellsmentioning
confidence: 99%
“…Hypoxia-induced autophagy has been demonstrated to be crucial for survival of liver CD133+ CSCs; more interestingly, in pancreatic CSCs, HIF-1 α -dependent autophagy is critical for the equilibrium between non-stem pancreatic cancer cells and pancreatic CSCs [59]. Indeed, autophagy was found to be upregulated in multiple human AML cell lines and primary blasts after prolonged exposure to hypoxia; also, inhibition of the late-stage of autophagy overcomes Leukemia Stem Cells (LSCs) survival and chemoresistance [60, 61]. This highlights the controversial role of autophagy in the death/survival of leukemic cells, in which reduced autophagy appears to be an adaptive mechanism that accelerates AML development [62].…”
Section: Autophagy and Cancer Stem Cellsmentioning
confidence: 99%
“…There are now several lines of evidence to suggest that PI3K signalling and mTORC1 itself are inhibited during mitosis. For example, phosphorylation of PKB at T308 and the PKB substrate PRAS40 at T246 are lost in mitosis [48], whilst phosphorylation of S6K, S6, and eukaryotic translation initiation factor 4E-binding protein 1 (4E-BP1) during mitosis is insensitive to PI3K inhibition or insulin stimulation [49]; together, this suggests that class I PI3K signalling is inhibited during mitosis [48]. Certainly, mutationally activated PI3K (p110CAAX) prevents the transcription of CCNB1 and PLK1, resulting in failure of cytokinesis [50], providing a rationale for repressing PI3K in mitosis.…”
Section: Cdk1 Inhibits Mtorc1 In Mitosis Insulating It From Nutrient Statusmentioning
confidence: 99%
“…It has been argued that because expression of a phospho-null mutant of the putative CDK1 sites on TSC1 impaired P-S6K (T389) phosphorylation relative to wild type, CDK1 phosphorylation of TSC1 stimulates mTORC1 signalling [51]; however, this was not evaluated in mitotic cells. In addition, PLK1 has been shown to phosphorylate TSC1, and this was proposed to promote mTOR localisation to lysosomes [49]. Others have argued that PLK1 decreased lysosomal association of mTORC1 [52]; certainly, recent studies have also shown that mTORC1 is not localised to lysosomes during mitosis [4,17].…”
Section: Cdk1 Inhibits Mtorc1 In Mitosis Insulating It From Nutrient Statusmentioning
confidence: 99%
“…Phosphoproteomic analysis indicates that ATR may directly phosphorylate TSC1 (Matsuoka et al, 2007). Phosphorylation of TSC1 would in turn activate mTORC1 Li et al, 2018). While it is mostly nuclear, multiple recent publications have shown a small fraction of ATR in the cytoplasm (Hilton et al, 2016;Postigo et al, 2017).…”
Section: Atr Activates Mtorc1 To Increase Nucleotide Synthesismentioning
confidence: 99%